PENANAMAN NILAI KARAKTER REMAJA MELALUI PERMAINAN TRADISIONAL - Ery Wati Nurdiana (Jurnal Sains Riset, 2020)
Teenagers are the successor of the nation that we must prepare all their needs both physically and spiritually. Becoming a reliable national successor is not only demanded by high knowledge or extraordinary skills but how to create a successor of the nation of Indonesia with character ?. The cultivation of character nowadays is very important and urgent because the influence of the progress of the globalization era offers many advantages which also have a negative impact. Humans tend to choose to live individually and are more selfish and material. Lack of communication with others will make someone difficult to interact. Cultivation of characters in adolescents can be done through traditional games, this has been done by Misbach (2006) of the Indonesian University of Education entitled "The Role of Educative Traditional Games in Contributing to Forming Nation Character and Identity" His conclusion was "Traditional games have a role which is very important and the formation of national character and identity, many traditional games overlap with local characters and wisdom which become the view of the life of the tribe where these characters are starting to fade little by little " For this reason researchers are very interested in conducting research on "The Role of Traditional Aceh Games in Forming Youth Character" The location of this study is in Mukim Sungai L abundant, Sukamakmur district. Aceh Besar ... This research aims to find out the factors that cause the traditional games of Aceh to disappear and illustrate the values of traditional games in building teenage characters. This research uses a descriptive approach and qualitative methods. With the technique of collecting data documentation, observation and interviews. The subject of this research is teenagers whose level of education is in junior high school. Data analysis is done by data reduction, data presentation and drawing conclusions. From the results of research that causes traditional games to be lost due to lack of socialization from parents, tight school hours and technological advancements and the characters embedded in these traditional games are honesty, courage, cooperation, obedience to rules and tolerance Keywords ; Traditional Game and a teenager Characters.